Pengaruh Dinamis Modal Manusia yang Menguasai Teknologi Informasi dan Komunikasi Terhadap Pertumbuhan Ekonomi - Bahri, Zainul (Badan Perencanaan Pembangunan, Penelitian dan Pengembangan Provinsi Sumatera Utara, 2024)
Research on the influence of Information and Communication Technology (ICT) and the Human Development Index (HDI) on economic growth has been carried out by many experts. However, only a few studies have tried to determine the influence of the interaction between ICT and HDI on economic growth. This research was conducted to determine the dynamic influence between ICT, HDI and the interaction between HDI and ICT on economic growth. This research is quantitative research using panel data in 10 provinces on the island of Sumatra for the period 2015 to 2022. GRDP at Constant Prices is used as a proxy for economic growth, ICT uses the ICT Index proxy, human capital uses the HDI proxy. The SYS GMM method was chosen to see the dynamic influence of the independent variable on the dependent variable, based on the results of the Sargan test which was carried out to determine whether the model used was valid or not as well as testing the consistency of GMM estimates using the Arellano Bond test. The three models used in this research are consistent and there is no autocorrelation in the first difference error. As a result, ICT, HDI and the interaction between HDI and ICT have a positive effect on economic growth, namely increasing ICT, HDI and the interaction between HDI and ICT can increase economic growth. ICT increases access to economic opportunities, education, and social participation, and supports inclusivity. Meanwhile, through resource efficiency, environmental management and continuous innovation, technology contributes to sustainable economic growth. To maximize these benefits, supporting policies are needed, namely: increasing ICT access and infrastructure, developing digital skills, protecting workers and creating new jobs, overcoming digital inequality through digital inclusion programs, developing innovation and research policies, social protection and strengthening security social, regulatory and adaptive policies. Keywords:1.ICT Index 2.Economic Growth 3.Human Development Index 4.Dynamic influence 5.GMM